External Quality Of Merawangarab Chicken Eggs With Different Genetic Composition - Rafif Nurwansyah; Harini Nurcahya; Ikhsan Matodang; Sri Darwati (Journal of Tropical Biodiversity, 2025)
Eggs, as a food ingredient, possess complete nutritional value that is beneficial for human health, are readily available, affordable, and popular with the public. Likewise, hatching eggs provide the nutrients needed for the development of chicken embryos. Therefore, eggs for consumption as food and hatching eggs. The external quality of eggs is one indicator of egg quality. Merawang chickens and arab chickens are local Indonesian chickens. Crossbreeding of the two chickens is expected to produce superior offspring in production and egg quality. This study aimed to evaluate the external quality of merawangarab crossbred chicken eggs with different merawangarab genetic compositions (M), namely 25% M, 50% M, 62.5% M, and 75% M with a total of 30 hens. The materials used were eggs from merawangarab crossbred chickens. This study used a randomized block design (RAK) and continued with Tukey's further test. The external quality of eggs observed was shape index, egg weight, shell weight, and shell ratio. Different genetic compositions did not affect the external quality of merawangarab crossbred chicken eggs. Eggs from four crossbred merawangarab chickens were (25% M, 50% M, 62.5% M and 75% M) classified as small